Penggunaan Media Pecahan Untuk Meningkatkan Pemahaman Konsep Dasar Pecahan Pada Siswa Kelas VI SDK St. Arnoldus Penfui - Rosario Bura Balamiten; Wara Sabon Dominikus (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2021)
Student-centered learning allows students to be actively involved in learning. One way to activate students in learning is the use of learning media that is in accordance with the material or concept being learned. Learning media can be used, including visual media, audio media, audio-visual media and even media originating from school environments that have educational value. The use of media in mathematics learning is expected that students will better understand and understand the concepts being learned. The research is a Classroom Action Research (PTK). This research was conducted to improve understanding of the basic concepts of fractions through the use of fraction media in learning. The research subjects were 26 grade VI students. The research data consisted of data from observations and test results. Data were analyzed descriptively. Students' understanding of the basic concepts of fractions and the accuracy of students using fraction media increased from cycle I to cycle II. These results indicate that the use of fractions media improves students' understanding of the basic concepts of fractions. For this reason, learning mathematics in elementary schools should use learning media that is in accordance with the concepts being studied.